2022
DOI: 10.1109/access.2021.3138274
|View full text |Cite
|
Sign up to set email alerts
|

DC Bus Voltage Control of Wind Power Inverter Based on First-Order LADRC

Abstract: The wind power grid-connected inverter system has the characteristics of non-linearity, strong coupling, and susceptibility to grid voltage fluctuations and non-linear loads. To obtain the ideal control effect, the improved linear active disturbance rejection controller (LADRC) controls the voltage outer loop. Firstly, the mathematical model of the wind power grid-connected inverter is analyzed, on this basis, a linear active disturbance rejection control based on the reduced-order linear extended state observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Another advantage of the improved LESO controller is that it is insensitive to the slight variation of control parameters which inherits from the ADRC method. Therefore, in order to simplify the tuning of control parameters, the PD variables can be selected as k p ¼ v 2 c , k d = 2v c , and v c is the bandwidth of the controller [31,32]. As a result, the input variable u is rewritten as (7), and the transfer functions of each variable is obtained,…”
Section: Controller Design For the Elasmentioning
confidence: 99%
“…Another advantage of the improved LESO controller is that it is insensitive to the slight variation of control parameters which inherits from the ADRC method. Therefore, in order to simplify the tuning of control parameters, the PD variables can be selected as k p ¼ v 2 c , k d = 2v c , and v c is the bandwidth of the controller [31,32]. As a result, the input variable u is rewritten as (7), and the transfer functions of each variable is obtained,…”
Section: Controller Design For the Elasmentioning
confidence: 99%
“…Despite the aforementioned developments in trajectory-following control, how to deal with AGEV system nonlinearity and internal and external disturbances remain as difficulties. Recently, ADRC technology has been shown to possess the ability to deal with these challenges, and the ADRC retains the advantages of simple computation, structural simplicity strong versatility, and strong robustness against disturbance compensation, which can improve system stability, reliability, and response speed [18][19][20][21][22][23][24]. Recently, several efforts have been brought forward in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several efforts have been brought forward in this respect. An active disturbance rejection controller is introduced in active suspension system control of half-tracked vehicle, total disturbances can be eliminated by switch extended state observer [21]. In [23], a dual-loop control strategy based on active disturbance rejection control is designed to attenuate external and internal disturbances of single-stage three-phase isolated matrix rectifiers (TIMRs).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the authors propose a novel wind field model; this model is employed to prove the effectiveness of the controller under the action of wind disturbance. Research by Yuan and Zhao et al [16,17], aiming at the problem of grid voltage fluctuation in power grid systems such as wind power grid-connected inverters, proposed an improved LADRC controller to improve the disturbance observation accuracy of the system by reducing the phase lag of the observer. The results showed that the improved method has better rapidity and immunity.…”
Section: Introductionmentioning
confidence: 99%